2006
DOI: 10.1002/prot.21033
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional evolution of transthyretin and transthyretin‐like proteins

Abstract: Transthyretin (TTR) is a tetrameric protein involved in the distribution of thyroid hormones in vertebrates. The amino acid sequence of TTR is highly conserved across vertebrates. Hypothetical TTR-like proteins (TLPs) were inferred from the identification of genes in nonvertebrate species. Here, we identified five motifs defining TLPs and three motifs defining both TTRs and TLPs. These motifs were mapped onto structurally conserved and functionally important regions of TTRs. These motifs were used to build hid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
77
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(83 citation statements)
references
References 69 publications
(89 reference statements)
6
77
0
Order By: Relevance
“…Another protein spot (ATF1; At1g21770; SSI>) was identified as a closely related homolog of a recently crystallized minimal acetyl transferase (ATF2; At1g77540; SSI>; Tyler et al, 2006). The single Arabidopsis transthyretin-like protein (TLP; At5g58220) is homologous to mammalian transthyretin, a transport protein for vertebrate hormones (Eneqvist et al, 2003;Hennebry et al, 2006aHennebry et al, , 2006b. Interestingly, the full-length protein contains a predicted PTS2 (RLx 5 HL) outside of the N-terminal domain in a linker region that connects two enzymatic domains, whereas two alternative splice variants from Arabidopsis lack the putative targeting signal ( Figure 3A; see Supplemental Figure 3P online; Hennebry et al, 2006a;Ramazzina et al, 2006).…”
Section: Novel Plant Peroxisomal Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another protein spot (ATF1; At1g21770; SSI>) was identified as a closely related homolog of a recently crystallized minimal acetyl transferase (ATF2; At1g77540; SSI>; Tyler et al, 2006). The single Arabidopsis transthyretin-like protein (TLP; At5g58220) is homologous to mammalian transthyretin, a transport protein for vertebrate hormones (Eneqvist et al, 2003;Hennebry et al, 2006aHennebry et al, , 2006b. Interestingly, the full-length protein contains a predicted PTS2 (RLx 5 HL) outside of the N-terminal domain in a linker region that connects two enzymatic domains, whereas two alternative splice variants from Arabidopsis lack the putative targeting signal ( Figure 3A; see Supplemental Figure 3P online; Hennebry et al, 2006a;Ramazzina et al, 2006).…”
Section: Novel Plant Peroxisomal Proteinsmentioning
confidence: 99%
“…The single Arabidopsis transthyretin-like protein (TLP; At5g58220) is homologous to mammalian transthyretin, a transport protein for vertebrate hormones (Eneqvist et al, 2003;Hennebry et al, 2006aHennebry et al, , 2006b. Interestingly, the full-length protein contains a predicted PTS2 (RLx 5 HL) outside of the N-terminal domain in a linker region that connects two enzymatic domains, whereas two alternative splice variants from Arabidopsis lack the putative targeting signal ( Figure 3A; see Supplemental Figure 3P online; Hennebry et al, 2006a;Ramazzina et al, 2006). By MS sequencing of three tryptic peptides covering major parts of the linker region, including the putative PTS2, the TLP homolog identified in Arabidopsis peroxisomes was demonstrated to represent the full-length protein, strengthening the idea that the internal PTS2 peptide targets full-length TLP to peroxisomes (Figure 3).…”
Section: Novel Plant Peroxisomal Proteinsmentioning
confidence: 99%
“…The nitrocellulose membrane was blocked for 1 h with 5% non-fat dried milk in tris-buffered saline (TBS) and incubated with primary antibody against TG (Sigma, St. Louis, MO, USA)/TTR (Abcam, USA) at 37 • C for 2 h. The blots were washed six times for 30 min with tris-buffered saline Tween-20 (TBST) and then incubated with AP-conjugated secondary antibody at 37 • C for 1 h. After that the blots were washed six times again, they were developed using a BCIP/NBT Kit (AMRESCO, USA). TTR is considered as an evolutionarily conserved serum protein (Hennebry et al, 2006;Buxbaum and Reixach, 2009 (Morgado et al, 2007). Using a rabbit antihuman TG serum that cross-reacted with lampreys (Lampetra appendix) TG, Western blotting detected a single protein of ∼226 kDa (Manzon and Youson, 2002).…”
Section: Protein Extraction and Western Blot Analysismentioning
confidence: 99%
“…Page 4 of 44 A c c e p t e d M a n u s c r i p t 4 proteins (TLPs) has been identified in bacteria, plants and animals including nonvertebrates and vertebrates (Eneqvist et al, 2003, Hennebry et al, 2006a. It has been suggested that the TTR gene, only present in vertebrates, probably arose as a results of a duplication of the ancestral TLP gene (Hennebry et al, 2006a, Prapunpoj et al, 2000, Richardson, 2002.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the TTR gene, only present in vertebrates, probably arose as a results of a duplication of the ancestral TLP gene (Hennebry et al, 2006a, Prapunpoj et al, 2000, Richardson, 2002. Existent studies indicate an overall structural conservation between TLP and TTR (Hennebry et al, 2006b, Lundberg et al, 2006 however no evidence of TH binding ability could be found for TLP (Eneqvist et al, 2003).…”
Section: Introductionmentioning
confidence: 99%